A 2D finite element/boundary element method applied to practical 2D and 3D scattering problems - Meyer, F.J.C; Davidson, D.B (Second International Conference on Computation in Electromagnetics, 1994)
The finite element/boundary element (FE/BE) method for solving electromagnetic (EM) problems has been investigated and implemented. A careful validation of the method (using both canonical problems that can be computed analytically and measured data from complex real-world problems) has been performed. The FE/BE has been applied to otherwise intractable and important problems in RCS reduction evaluations. Line source radiation close to human beings as well as power dissipated in humans near line sources has also been considered using the FE/BE method. Some adaptive finite element methods used to improve the computational efficiency of the FE/BE method are being investigated.